Enhancing Cultural Intelligence: The Roles of Implicit Culture Beliefs and Adjustment. Issue 1 (26th February 2016) - Chao, Melody Manchi; Takeuchi, Riki; Farh, Jiing‐Lih
Abstract : Although international experience has been proposed as an important factor contributing to the development of cultural intelligence (CQ), its effect on CQ has often been assumed. Through a contact hypothesis framework, this study advances our understanding of CQ. It examines the process through which CQ changes occur against the backdrop of international exchanges. University students who were enrolled in an international exchange program with partners worldwide participated in this study. Using a 3‐wave time‐lagged design, we found that implicit culture beliefs (the beliefs about fixedness or malleability of cultural attributes) influenced intercultural rejection sensitivity, which impacted the cross‐cultural adjustment of sojourning students and their subsequent CQ. Specifically, we found that cross‐cultural adjustment experiences, particularly in the social domain, play an important role in influencing CQ. Findings from this study raise novel research questions and underscore the need for more empirical work in this area. Theoretical and practical implications are discussed.